2015
DOI: 10.3892/or.2015.4462
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA7 inhibits cell invasion and metastasis of LoVo human colorectal cancer cells through PI3K/Akt signaling

Abstract: Abstract. The α7 neuronal nicotinic receptor gene (CHRNA7) is widely expressed in both the brain and periphery whereas its encoding protein of α7 neuronal acetylcholine receptor (α7nAChR) belongs to the nicotinic acetylcholine receptor family. Considerable evidence suggests that α7nAChR plays an important role in chronic inflammatory and neuropathic pain signaling and thus has been proposed as a potential target for treating cognitive deficits in patients with schizophrenia, attention deficit hyperactivity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Liu et al reported that miR-596 could modulate melanoma growth via regulating cell survival and death 34 . Xiang et al found that CHRNA7 inhibited cell invasion and metastasis of LoVo human colorectal cancer cells by PI3K/Akt signaling 35 . Dai et al revealed that miR-424-5p promoted the proliferation and metastasis of colorectal cancer via directly targeting SCN4B 36 .Yuan et al identified a novel splice variant of AC3-33 (C3orf33) in breast cancer 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that miR-596 could modulate melanoma growth via regulating cell survival and death 34 . Xiang et al found that CHRNA7 inhibited cell invasion and metastasis of LoVo human colorectal cancer cells by PI3K/Akt signaling 35 . Dai et al revealed that miR-424-5p promoted the proliferation and metastasis of colorectal cancer via directly targeting SCN4B 36 .Yuan et al identified a novel splice variant of AC3-33 (C3orf33) in breast cancer 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In pathway enrichment analysis for DEGs was performed. Genes such as ALDOB (aldolase, fructose-bisphosphate B) [68], KHK (ketohexokinase) [69], CHRNA7 [70], GSTA3 [71], APOA1 [72], CEBPA (CCAAT enhancer binding protein alpha) [73], PCK1 [74], ATP1A1 [75], CLCA1 [76], EMB (embigin) [77], SLC22A18 [78], FUT5 [79] and ITLN1 [80] were linked with progression of various cancer types, but these genes might be identified with growth of NET. Polymorphic genes such as GSTA1 [81], GSTA2 [82], MGST1 [83], NAT2 [84], SULT1A2 [85], SULT2A1 [86], UGT1A6 [87], UGT2B15 [88], UGT2B17 [89], ABCC2 [90], FUT2 [91] and APOB (apolipoprotein B) [92] were liable for progression of various cancer types, but these polymorphic genes might be diagnosed with growth of NET.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of nAChRs in non-neuronal cells elicits the non-ionic signaling events that regulate protein phosphorylation and dephosphorylation, which is a novel function of nAChR subunit proteins in non-excitable cells. Activation of α7nAChR can activate p38 MAPK, AKT, RAS/RAF/MEK/ERK and JAK2 ( 49 , 50 ). In the present study, we determined the expression of phosphorylated STAT3, NF-κB p65 and PI3K p85 in THP-derived macrophages with or without α7nAChR knockdown (TMa7 −/− and TM).…”
Section: Discussionmentioning
confidence: 99%